2016
DOI: 10.1371/journal.pone.0152089
|View full text |Cite
|
Sign up to set email alerts
|

Migration, Remittances and Nutrition Outcomes of Left-Behind Children: A National-Level Quantitative Assessment of Guatemala

Abstract: Historically, Guatemalans have suffered high rates of poverty and malnutrition while nearly ten percent of their population resides abroad. Many Guatemalan parents use economic migration, mainly international migration to the United States, as a means to improve the human capital prospects of their children. However, as this investigation shows, the timing of migration events in relation to left-behind children’s ages has important, often negative and likely permanent, repercussions on the physical development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 55 publications
1
36
0
Order By: Relevance
“…The present study broadly supports the previous findings that parental migration was not significantly detrimental to child nutrition [13,16,22,36] and even confirm the benefits of paternal migration on early childhood nutrition of rural children [13,37,38], despite contrary results found in other studies [5,18,39]. A decreasing difference in early childhood nutrition between children with various parental migration statuses was shown in recent years, and in the survey in 2016, no significant differences in risks of stunting, underweight, and wasting were detected between them.…”
Section: Discussionsupporting
confidence: 92%
“…The present study broadly supports the previous findings that parental migration was not significantly detrimental to child nutrition [13,16,22,36] and even confirm the benefits of paternal migration on early childhood nutrition of rural children [13,37,38], despite contrary results found in other studies [5,18,39]. A decreasing difference in early childhood nutrition between children with various parental migration statuses was shown in recent years, and in the survey in 2016, no significant differences in risks of stunting, underweight, and wasting were detected between them.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, Ponce et al (2011) also in Ecuador and using a different instrumental variable techniquefound no effect of remittances on nutrition. In Guatemala, Davis and Brazil (2016) showed that international remittances have no influence on the nutritional status of children left behind (aged 3 or less), which could indicate that fathers are not able to improve their economic situation soon enough to make an impact on their children's nutrition. Finally, a panel study in Mexico showed that migration (including remittances) had a detrimental effect on children's height-for-age (Nobles 2007).…”
Section: Effects Of Remittances On Food Securitymentioning
confidence: 99%
“…There is evidence of positive impacts on the children's nutritional condition (10,40), the diet of older adults (18), the increase of weight at birth (3,19), the weight conditions of children younger than 15 years old (9) and the decrease in the prevelance of growth retardation (62,42). However, some studies reported negative effects such as the worsening of the diet of the household members (51,63), malnutrition among pre-schoolers (64), children younger than 18 years old would present growth retardation (63,65), the migrants' wives (15), and children between 1 and 5 years old were overweight (64), a part from the abandonment of exclusive breastfeeding (10).…”
Section: Effect Of Emigraton or Return Of A Family Member On Health Cmentioning
confidence: 99%
“…Some studies did not find evidence that remittances affected health outcomes such as the proportion of children who attend school with malnutrition (73), consumption of health services (35), access to public health services (31), health expenditure of households (12), child mortality (65,67) and that measure the long-term health condition of children (growth retardation, low weight), the prevalence of respiratory diseases and of diarrhea (33).…”
Section: Effect Of Transfers On Health Conditions Of the Household Inmentioning
confidence: 99%